Pelatihan Penulisan Artikel Ilmiah untuk Meningkatkan Kompetensi Profesional Guru SMA Negeri 2 Merauke Provinsi Papua - Rezky Uspayanti; Desy Kumala Sari; Fredy Fredy (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The aims of this community service is to improve teachers’ professional competence through training for writing scientific article and classroom action research. The method used was training method with online and offline form. This training was done on September until November 2021. The target was the teachers of Senior High School 2 Merauke province Papua. There were some steps of this community service namely observation, giving material, and monitoring to know the progress of the program. After that training was done, the participants were give the questionnaires that consisted of ten statements. Based on the result of questionnaires, the teachers of Senior High School 2 Merauke gave positive responses namely the responses on very good, good, and neutral category. The result showed that the training can help the teachers in doing classroom action research and scientific research, improving the motivation in writing, helping the job, and improving the professional competency of the teacher.